Effect of resistant starch (Hi-maize) on the survival of Lactobacillus acidophilus microencapsulated with sodium alginate. (March 2016) - Etchepare, Mariana de Araújo; Raddatz, Greice Carine; Cichoski, Alexandre José; Flores, Érico Marlon Moraes; Barin, Juliano Smanioto; Queiroz Zepka, Leila; Jacob-Lopes, Eduardo; Grosso, Carlos Raimundo Ferreira; de Menezes, Cristiano Ragagnin
Highlights: Hi-maize containing microcapsules improve protection of probiotics. The viability of the probiotic was enhaced under storage conditions. Hi-maize protected Lactobacillus acidophilus in gastrointestinal stress tests. Abstract: Resistant starch (Hi-maize) at a concentration of 1% was used for the microencapsulation of Lactobacillus acidophilus in alginate beads. Moist and freeze-dried microparticles were obtained. The addition of prebiotics did not increase the size of the moist particles. By contrast, the freeze-dried microparticles of alginate and alginate + Hi-maize had diameters of 114.51 and 78.49 µm, respectively. The Hi-maize provided better protection for the probiotics after exposure to simulated gastrointestinal juice for both the moist and the freeze-dried microparticles. Regarding the viability of the probiotic culture during storage, both treatments proved to be viable, with suitable values conferring probiotic effects (<6 log CFU g −1 ), with at least 30 days of stability in the freeze-dried form and 135 days in the moist form, both under storage at room temperature (25 °C).